2021
DOI: 10.2166/nh.2021.148
|View full text |Cite
|
Sign up to set email alerts
|

Relative impacts of increases of solar radiation and air temperature on the temperature of surface water in a shallow, eutrophic lake

Abstract: We monitored lake surface water temperatures from 1992 to 2019 in Lake Kasumigaura, a shallow lake in Japan. We hypothesized that increases of shortwave radiation had increased surface water temperatures and heat fluxes more than had the increases of air temperature. We used the heat flux analyses and the sensitivity analyses to test the hypothesis. The fluxes of solar radiation gradually increased during the study period in a manner consistent with the phenomenon of global brightening. The increase was especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Li et al 54 found modeled warming rates of 0.4−0.6 °C dec −1 for spring in four large subtropical shallow lakes in China between 1979 and 2017, with similar trends in the summer and homogeneous warming rates for all four lakes. Shinohara et al 55 found trends of 0.7 °C dec −1 in March and May (corresponding to September and November in the Southern Hemisphere), with similar trends in the summer for a temperate turbid shallow lake in Japan. Other studies have also found higher LSWT warming in spring than in summer.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Li et al 54 found modeled warming rates of 0.4−0.6 °C dec −1 for spring in four large subtropical shallow lakes in China between 1979 and 2017, with similar trends in the summer and homogeneous warming rates for all four lakes. Shinohara et al 55 found trends of 0.7 °C dec −1 in March and May (corresponding to September and November in the Southern Hemisphere), with similar trends in the summer for a temperate turbid shallow lake in Japan. Other studies have also found higher LSWT warming in spring than in summer.…”
Section: Resultsmentioning
confidence: 77%
“…Li et al found modeled warming rates of 0.4–0.6 °C dec –1 for spring in four large subtropical shallow lakes in China between 1979 and 2017, with similar trends in the summer and homogeneous warming rates for all four lakes. Shinohara et al found trends of 0.7 °C dec –1 in March and May (corresponding to September and November in the Southern Hemisphere), with similar trends in the summer for a temperate turbid shallow lake in Japan. Other studies have also found higher LSWT warming in spring than in summer. , In contrast, Winslow et al found cooling air temperature trends between February and May (corresponding to August and November in the Southern Hemisphere), with low water temperature warming rates for six shallow and small temperate lakes in the USA over a 35 year period, where the higher warming rates were found between September and December.…”
Section: Discussionmentioning
confidence: 81%
“…The increase in surface water temperatures also has implications for harmful algal blooms (HABs) in deep and shallow lakes [57]. Warmer temperatures can promote the growth and proliferation of the algae species responsible for HABs [58]. The thermal structure of the lakes can influence the effects of temperature on HABs.…”
Section: Discussionmentioning
confidence: 99%
“…The average air temperature increased by 4ºC from 21ºC, but the water temperature decreased (0.2-1.5ºC). Shinohara et al (2021) reveal that surface water temperature is more sensitive to changes in shortwave radiation. Still, this theory does not occur in the Cikapayang River, whose conditions have changed significantly due to input from outside the system.…”
Section: River Water Qualitymentioning
confidence: 97%